The Effectiveness of the Thematic Village Program in Women Farmers' Groups: A Comparative Study of Two Villages in Tangerang Regency - Hilva Zakiatul Rahmatian; Kandung Sapto Nugroho (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The Thematic Village Program is a local government strategy to foster village self-reliance by empowering Women Farmer Groups (Kelompok Perempuan Tani/KWT), yet its outcomes vary considerably across localities. This study measures and compares the effectiveness of the Thematic Village Program implemented by the KWT of Sodong Village and the KWT of Bojong Renged Village, Tangerang Regency, using Campbell's five program-effectiveness indicators. A comparative-descriptive quantitative approach was applied through total sampling of the entire population of 28 KWT members (13 respondents from Sodong and 15 from Bojong Renged), using a 26-item Likert-scale questionnaire that had passed validity (r count > 0.374), reliability (Cronbach's Alpha > 0.70), normality (Shapiro-Wilk, p > 0.05), and homogeneity (Levene, p > 0.05) tests. The actual-score calculation showed program effectiveness of 78.40 percent in Sodong and 71.15 percent in Bojong Renged, both falling into the good category yet short of the very-good threshold. An Independent Samples t-Test revealed statistically significant differences in three of the five indicators—satisfaction with the program, input-output level, and overall goal attainment (p < 0.05)—with Sodong consistently outperforming. These findings indicate that harvest-revenue management and administrative mentoring are the principal factors differentiating program effectiveness between areas with otherwise similar socio-economic characteristics.